The pivotal role of 5-lipoxygenase-derived LTB4 in controlling pulmonary paracoccidioidomycosis. - Patrícia Campi Santos; Daniel Assis Santos; Lucas Secchim Ribeiro; Caio Tavares Fagundes; Talles Prosperi de Paula; Thiago Vinícius Avila; Ludmila de Matos Baltazar; Mila Moreira Madeira; Rosana de Carvalho Cruz; Ana Carolina Fialho Dias; Fabiana Simão Machado; Mauro Martins Teixeira; et al. (Public Library of Science (PLoS), 2013)
Leukotrienes (LTs) produced from arachidonic acid by the action of 5-lipoxygenase (5-LO) are classical mediators of inflammatory responses. However, studies published in the literature regarding these mediators are contradictory and it remains uncertain whether these lipid mediators play a role in host defense against the fungal pathogen Paracoccidioides brasiliensis. To determine the involvement of LTs in the host response to pulmonary infection, wild-type and LT-deficient mice by targeted disruption of the 5-lipoxygenase gene (knockout mice) were studied following intratracheal challenge with P. brasiliensis yeasts. The results showed that infection is uniformly fatal in 5-LO-deficient mice and the mechanisms that account for this phenotype are an exacerbated lung injury and higher fungal pulmonary burden. Genetic ablation or pharmacological inhibition of LTs resulted in lower phagocytosis and fungicidal activity of macrophages in vitro, suggesting that deficiency in fungal clearance seems to be secondary to the absence of activation in 5-LO(-/-) macrophages. Exogenous LTB4 restored phagocytosis and fungicidal activity of 5-LO(-/-) macrophages. Moreover, P. brasiliensis killing promoted by LTB4 was dependent on nitric oxide (NO) production by macrophages. Taken together, these results reveal a fundamental role for 5-LO-derived LTB4 in the protective response to P. brasiliensis infection and identify relevant mechanisms for the control of fungal infection during the early stages of the host immune response.